Factors influencing to the incidence of teenage pregnancy - Diana Novitadewi Budiharjo; Endah Marianingsih Theresia; Hesty Widyasih (Jurnal Kesehatan Ibu dan Anak, 2018)
highest adolescent births during the last four years compared to other districts. Teenage pregnancy has a negative impact on mother and baby. According to WHO, girls aged 10-14 years have a five times greater risk of dying in cases of pregnancy and childbirth than women aged 20-24 years. The aim of this study was to know the factors related to the incidence of teenage pregnancy in adolescent girls in Saptosari Health Center working area in 2017. This research used a cross-sectional study design. The sampling technique was purposive sampling with 67 girls in the working area of Saptosari Public Health Centre. The research instrument was in form of the questionnaire. The data were analyzed by using the Chi-Square test. Respondents in this study were at most 14-16 years old with age 11-15 year menarche and high school parent’s education level. The results of the Chi-Square test showed that factors significantly related to teenage pregnancy adolescent behavior were the level of knowledge p = 0.032 and the role of parents p = 0.036. Attitudes toward teenage pregnancy (p = 0.081) and peer roles (p = 0.100) were factors that not related to the incidence of teenage pregnancy factors influencing the incidence of teenage pregnancy among teenage girls in Saptosari. Factors related to teenage pregnancy were knowledge of teenage pregnancy and parent’s role.